THE ROLE OF LECTURERS IN NURSING EDUCATION - Siti Kholifah (Universitas Muhammadiyah Yogyakarta, 2015)
Lecturer has a big role in learning accomplishment of nursing students. The duty of nursing lecturers in the learning are required to have several competencies such as ability of knowledge mastery, ability of skills mastery and ability in the terms of attitude. Those three competencies must be possessed by lecturers in order to make students accomplish competencies in the form of competency of knowledge mastery, competency of skills mastery and competency of attitude. This article aims to describe the nursing lecturers’ roles in relation with learning process. This explanation hopefully can enhance lecturer’s knowledge in improving quality of learning which affects the accomplishment of nursing students as well. The accomplishment of nursing students’ competency can’t be separated from lecturers role in learning process, both in academic field and practical field (clinic). Those roles are as an educator, a guide, a leader, a communicator, a role model, an assessor, a counselor, a problem solver, an expertise, a facilitator, a motivator and an inspirator. Twelve roles of nursing lecturers in learning process are the elaboration of lecturers’ main role based on the role of nurse in nursing namely assessor, planner, implementer, and evaluators.Key words : lecturers’ role, nursing education